The Preparation and Use of Library Manpower - Asheim, Lester (1972)
Trends in library education and manpower utilization in general are briefly surveyed, with special reference to the official ALA Policy on Library Education and Manpower approved in July 1970. The trends are marked by general upgrading of standards and content of library education, resulting in a longer period of formal education with more room for intensive specialization; different kinds of preparation for different levels of responsibility; and a serious exploration of the ways in which paraprofessional or supportive staff can be utilized to release the librarian for more professional responsibilities. The Policy Statement is analyzed to show its support of most of these developments. A key concept is that the demands of the position should be the test of professional quality, and not the diploma held by the applicant. The hope is that the changes suggested will improve the quality of library service and the preparation for it and that this general improvement will be applicable also to such special fields as medical librarianship.